An examination of building societies in the context of financial liberalization and deregulation : Jamaica 1990-1995 - Johnson, Ann-Marie ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Reviews the origin and development of the societies in Jamaica (prior to 1990) and the factors influencing their growth. Discusses developments in the industry against the background of financial liberalization and the deregulation of the foreign exchange market.